Tolerance Education Model for Early Childhood (Study at Mutiara Ibu Integrated Early Childhood School, Purworejo) - Lestari, Sulastri; Najanuddin, Najanuddin; Aziz, Abdul (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
Mutiara Ibu Purworejo Integrated PAUD under the auspices of the Kasih Ibu Purworejo Foundation consists of Playgroup, Daycare, and Kindergarten services. This educational institution serves learners with more religious backgrounds than similar institutions in Purworejo Regency. From this, the author makes a scientific study to find out how the life of religious tolerance is taught to Learners who are still at an early age. The research approach used is Qualitative Research Method with Field Research, namely the author digs up information through Educators who are involved in learning and care. The data collection technique used is through interviews, observation, and documentation. Furthermore, the Data Validation Process is carried out by the Triangulation Method and Re-asking the Sources. The results of the research conducted state that the Steps for Cultivating Tolerance Values in Learners of Mutiara Ibu Purworejo Integrated PAUD are carried out through 4 things, namely (1) Introduction of attitudes that support tolerance, (2) Habituation of applying rules, (3) Character models, and (4) Parental Involvement through Parenting Activities.